Chromium Tolerance and Bioremoval by Cyanobacteria Isolated from Textile Mill Oxidation Pond in Pure and Consortia Form - Anubha Kaushik; Kamra Anjana; CP Kaushik; Bala Kiran (Journal of Applied Sciences and Environmental Management)
Two cyanobacterial species Nostoc calcicola HH-12 and Chroococcus minutus HH-11 isolated from a textile mill oxidation pond were examined individually and as consortium for their chromium(VI) tolerance and bioremoval from aqueous solutions. Both species were tolerant to the metal and showed significant increase (p<0.01) in concentration of chlorophyll and carotenoids at higher concentration of chromium, and the tolerance further in the consortium. Concentration of phycobilins also increased in the pure culture of Chroococcus and consortium was also higher in response to increasing chromium concentration in the medium. Chromium bioremoval potential was high in both species and the consortium was even more efficient in metal removal. Probable antioxidative role of carotenoids in metal tolerance have also been discussed. @JASEM